Primary Nocardia Infection Causing a Fluorodeoxyglucose-Avid Right Renal Mass in a Redo Lung Transplant Recipient - Sreeja Biswas Roy; Mitchell D. Ross; Pradnya D. Patil; Richard Trepeta; Ross M. Bremner; Tanmay S. Panchabhai (Case Reports in Transplantation)
Immunosuppression after lung transplantation may increase susceptibility to opportunistic infection and is associated with early and delayed deaths in lung transplant recipients. Factors that may predispose lung transplant recipients to opportunistic bacterial and fungal infections include prolonged corticosteroid use, renal impairment, treatment of acute rejection, and post-transplant diabetes mellitus. We present a unique case of a 63-year-old woman with diabetes mellitus who underwent redo lung transplantation. Three years after her right-sided single redo lung transplant, she presented with right-sided abdominal pain, nausea, and vomiting. Upon examination, computed tomography showed a 4.5 × 3.3 cm heterogeneous, enhancing right renal mass with a patent renal vein. Magnetic resonance imaging confirmed a T1/T2 hypointense, diffusion-restricting, right mid-renal mass that was fluorodeoxyglucose-avid on positron emission tomography. We initially suspected primary renal cell carcinoma. However, after a right nephrectomy, no evidence of neoplasia was observed; instead, a renal abscess containing filamentous bacteria was noted, raising suspicion for infection of the Nocardia species. Special stains confirmed a diagnosis of Nocardia renal abscess. Computed tomography of the chest and brain revealed no lesions consistent with infection. We initiated a long-term therapeutic regimen of anti-Nocardia therapy with imipenem and trimethoprim-sulfamethoxazole.